1991
DOI: 10.4141/cjas91-035
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of respirable dust and bioaerosols and identification of certain microbial types in a hog-growing facility

Abstract: a hog-growing facility. Can. J. Anim. Sci. 7I: 2'71-2'77.In order to assess the effects of ventilation rate, temperature, relative humidity and source of air on bioaerosol levels and dust with particle size < l0 pm, a total of 120 pigs housed in 12 pens in two separate rooms were used. Pigs averaged 30 kg initially and the trials were discontinued when2O% of the pigs were marketed. A six-stage Andersen sampler and a light scattering particle counter were used to determine bioaerosols and respirable dust (0.1-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 4 publications
0
13
1
1
Order By: Relevance
“…It can be assumed that as the strewn material became moister during the course of the trial because of a buildup of urine, the particles were increasingly bound and were not released into the atmosphere. Contrary to our original assumption that with increased humidity the generation of particles would be reduced, Butera et al (1991) found that the relative humidity in the stable had no effect on the generation of airborne particles.…”
Section: Discussioncontrasting
confidence: 98%
“…It can be assumed that as the strewn material became moister during the course of the trial because of a buildup of urine, the particles were increasingly bound and were not released into the atmosphere. Contrary to our original assumption that with increased humidity the generation of particles would be reduced, Butera et al (1991) found that the relative humidity in the stable had no effect on the generation of airborne particles.…”
Section: Discussioncontrasting
confidence: 98%
“…It is likely that the higher endotoxin concentrations (table 5) with increased humidity were due to prolonged bacterial survival times (Butera et al, 1991;Zucker et al, 2000). Generally, the natural half-life of airborne gram-negative bacteria ranges between a few minutes and perhaps an hour.…”
Section: Effects Of Humidity and Temperaturementioning
confidence: 99%
“…The influence of temperature on the physical decay of airborne particles has been studied in numerous articles, and the authors generally agree that the concentration of airborne particles is increased at low temperatures, probably due to a combined effect with low RH (Fišer & Král, 1969;Heber et al, 1988a;Butera et al, 1991). Curtis et al (1975a) quantified this relationship and found that the common logarithm of the number of bacterial colony-forming particles increased by 0.02 per degree Celsius decrease in median temperature for the day.…”
Section: Factors Influencing Aerosol Survival Transport and Concentrmentioning
confidence: 99%